Butter, flour, sugar, joy - Kartes, Danielle (Sourcebooks, 2023)
"The best baking starts with joy! Beloved celebrity cookbook author Danielle Kartes of the hit food blog Rustic Joyful Food tackles the baking world with Butter, Flour, Sugar, Joy, the ultimate baking book for everyone. A lot of people will tell you that baking is science-it requires precision and expertise and fancy kitchen gadgets. But in this book you will find easy-to-follow one-bowl wonders that set the stage for joy! At the heart of baking is the sweet sense of connection, of sharing a treat with someone you love. And that's something anyone can master. Every chapter of Butter, Flour, Sugar, Joy features simple, delicious dessert recipes-including Danielle's perfect dump-and-stir cake method, which allows you to create showstopper confections without all the fuss. Welcome to the world of Butter, Flour, Sugar, Joy-where messes are encouraged and the comfort of casual home baking is the main course"--